The matter of the method in personalist bioethics view. - Pessina, Adriano (Medicina e Morale, 2004)
The author faces the matter of the method in the personalist bioethical perspective. The Author underlines - after having clarified that a specific method in bioethics doesn't exist because the bioethics assumes the specific method of investigation of the ethical reflection from which it depends - that the originality of the bioethics, in comparison to the ethics, is in its contents, that is actions and processes mediated from the scientific knowledge and the technological routine. A particular reflection is proposed about the triangular method by E. Sgreccia in his known Manuale di Bioetica. This method is distinguished from the proceduralism of other perspectives, either for its contents, rooted in a substantialist conception of the human person or for its critical, or dialectical, structure. The analogous meaning of truth emerges in the connection between the medical-scientific data, the anthropological data and the ethical step: in fact, the truth is a concept not limited only in the field of the experimental sciences but also effective at the ethical level. In such a sense, the bioethics rises like a discipline that it forms through a way (the triangle) that it has its result whereas the judgment of conscience is formulated on the grounds of acquired and integrated truths, and of different goods at stake. The prescriptive step, that it is decisive in bioethical inquiry, is not assimilable to a pure deduction from the moral principles but it forms inside a complex theoretical itinerary that accounts for the different approaches to the reality.